TATKALA AGAMA BERUBAH JADI BENCANA - Arif Nuh Safri (Postgraduate State Islamic Institute (IAIN) Metro, 2015)
The essence of religion is sacral and holy, but the problems and conflicts will arise when the understanding of religion is also considered sacred and holy by his followers. Resulting in a gray zone or obscurity between religion and religious thought. Therefore, through this article the author will explain how religion can be a scary and dangerous figure, or even become a terrible humanitarian disaster. In short, this kind of thing happens by nature and attitude of religious exclusiveness that leads to truth claims and at the same time accuse others as a heretic, infidel and must be fought. Through this same article, the authors provide a solution for the disaster, is to revive the culture or civilization religious dialogue, and openness in accepting differences, even more than just openness, every religious believer expected to have an ideology of pluralism.